History, historical method, and science: The History at Deanship of Veterinary Sciences of the Universidad Centroccidental Lisandro Alvarado (1964-2024) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
History, a science that enables societies to understand their evolution, strengthen their identity, and gain selfknowledge, plays a crucial role in shaping the consciousness of professionals in various disciplines.Its study requires rigorous methods that guarantee the accuracy of the facts and their indepth analysis in social, cultural, political, and economic contexts, offering a broad view of the world and, in some cases, delegitimizing or legitimizing social structures. Historical research, as a science, applies scientific methods that can range from searching for sources to constructing explanatory models, highlighting the dynamic interaction between the past, present, and what might be expected in the future. In this context, the history of science and professions emerges as a field that explores the trajectory of scientific and technological knowledge in its intrinsic relationship with environmental factors, giving way to the most modern vision of the history and sociology of science, which allows for an understanding of the importance of professional action in the processes of construction and transformation of society. Thus, we take a stroll through the history of science in Venezuela and, in particular, through the historiography of veterinary medicine in this country.
Keywords: History; scientific knowledge; historical research; veterinary medicine